Insights Into Amentoflavone: A Natural Multifunctional Biflavonoid - Xiong, Xifeng; Tang, Nan; Lai, Xudong; Zhang, Jinli; Wen, Weilun; Li, Xiaojian; Li, Aiguo; Wu, Yanhua; Liu, Zhihe (Frontiers in Pharmacology, 2021)
Amentoflavone (AMF) is an active phenolic compound isolated from Selaginella tamariscina over 40 years. AMF has been extensively recorded as a molecule which displays multifunctional biological activities. Especially, AMF involves in anti-cancer activity by mediating various signaling pathways such as ERK, NF-κB and PI3K/Akt, and emerges anti-SARS-CoV-2 effect via binding towards the main protease (Mpro/3CLpro), spike protein RBD and RNA-dependent RNA polymerase (RdRp) of SARS-CoV-2. Therefore, AMF is considered to be a promising therapeutic agent for clinical research. Considering the multifunction of AMF, the current review comprehensively discuss the chemistry, the progress in its diverse biological activities, including anti-inflammatory, anti-oxidation, anti-microorganism, metabolism regulation, neuroprotection, radioprotection, anti-angiogenesis, musculoskeletal protection and antidepressant, specially the fascinating role against various types of cancers. In addition, the molecular mechanisms underlying the activities of AMF, the molecular docking simulation of AMF through in silico approach and anti-SARS-CoV-2 effect of AMF are discussed.